A design approach for thermal enhancement in heat sinks using different types of fins: A review - Gaikwad, Abhijeet; Sathe, Anilkumar; Sanap, Sudarshan (Frontiers in Thermal Engineering, 2023)
This article provides an in-depth overview of thermal heat sink design and optimization. Heat transfer enhancement strategies are discussed in detail, followed by fin design trends and geometries, and a discussion on different fin configurations and their merits is also presented. Important results and findings of experiments concerning the design and optimization of fin geometries have been summarized. For complex heat dissipation applications, researchers have been studying different fin arrangements especially, inclined fins, to maximize the performance of the heat sinks. Along with innovative fin designs, microchannels for heat dissipation are gaining attention due to their efficiency and easy manufacturability. Recent advances in this domain have been discussed. New components are becoming more compact and advanced as a result of technological breakthroughs in electronics and control systems; hence, the use and optimization of heat sinks for modern applications are also discussed in this article.